Alpinia oxyphylla Miq. Extract Prevents Diabetes in Mice by Modulating Gut Microbiota - Yiqiang Xie; Man Xiao; Yali Ni; Shangfei Jiang; Guizhu Feng; Shenggang Sang; Guankui Du (Journal of Diabetes Research)
Recently, the role of gut microbiota in the development of obesity and type 2 diabetes mellitus (T2DM) has been highlighted. We performed an 8-week administration protocol on T2DM (C57BL/6J db-/db-) mice and fecal samples were collected. Comparisons of fecal bacterial communities were performed between db-/db- mice and normal mice (DB/DB) and between the db-/db mice treated and untreated with AOE using next-generation sequencing technology. Our results showed that the db-/db-AOE group had improved glycemic control and renal function compared with the db-/db-H2O group. Compared with the db-/db-H2O group, AOE administration resulted in significantly increased ratio of Bacteroidetes-to-Firmicutes in db-/db- mice. In addition, the abundance of Akkermansia was significantly increased, while Helicobacter was significantly suppressed in the db-/db-AOE group compared with the db-/db-H2O group. Our data suggest that AOE treatment decreased blood glucose levels and significantly reduced damage of renal pathology in the T2DM mice by modulating gut microbiota composition.